Pigment Network Analysis in Melanoma and Nevi: Retrospective Study from Snippets to Full Dermoscopic Images - Kremer, Noa; N. Dana, Isabella; Chousakos, Emmanouil; M. Pastore, Larissa; C. Halpern, Halpern; W. Dusza, Stephen; Weber, Jochen; Reiter , Ofer; Lallas, Aimilios; Navarrete-Dechent, Cristian; Braun, Ralph; Rabinovitz, Harold; et al. (Dermatology Practical & Conceptual, 2025)
Introduction: Atypical network is a dermoscopic criterion that helps in the diagnosis of melanoma. Despite its importance, the interpretation of atypical networks varies widely among experts.Objective: This study examined the impact of viewing the whole lesion versus viewing foci of pigment network (i.e., snippets) in isolation from within the lesion on expert classification of pigment network in dermoscopic images.Method: Six dermoscopy experts, blinded to the diagnosis, each evaluated a total of 92 images (80 nevi and 12 melanomas) for the presence of typical versus atypical pigment network. While 57% of images had consistent classification of the network between whole lesion and snippets, 43% shifted the network classification between the snippet to the whole lesion view. Melanomas were more prone than nevi to intra-rater discrepancy between whole lesion and snippets (54.2% vs. 41.7%; odds ratio (OR): 1.65; 95% confidence interval (CI): 1.11–2.47). The inter-observer agreement was higher for the snippet view (65.22%) than for the whole lesion view (55%).Results: These findings suggest that both the objective morphology of the pigment network and the subjective interpretation of the network in context with other features within the lesion influence expert classification of pigment network.Conclusion: Factors such as the variability in the distribution, thickness, and color of network lines, overall pattern, and other dermoscopic structures likely contributed to the classification changes.